Self-efficacy of General English Lecturers after a Home-base Policy Change in an English Department in an Indonesian University - Ahmad Munir (Teacher Training and Education Faculty, Widya Gama Mahakam Samarinda University, 2020)
Background: Teachers' self-efficacy has a role in the success of the teaching and learning process in the classroom. Yet, the self-efficacy of general English lecturers in the context of higher education has rarely been investigated. Methodology: This article reports a study that describes the self-efficacy of former general English lecturers as an implementation of the general English lecturers' home-based policy in the English Department in a university in Surabaya and explains the reasons why they have such self-efficacy. Eight former general English lecturers who had been assigned as skills and contents lecturers in the English department participated in this study. Data were collected through three questionnaires and focused group discussions. Findings: The results of this study indicated that the participants reported high self-efficacy in engaging with students, managing classes, using instructional strategies, using English, and using pedagogical competence, even though there was different self-efficacy, from low to moderate, for some items in the questionnaires. These lecturers reported that they had high self-efficacy in many items in the questionnaires because of students' English competence, the subject matter factor, students' characteristics, and the working environment in the English department. Conclusion: In conclusion, a change in self-efficacy of the general English lecturers occurred along with the teaching experiences of these lecturers in a new teaching context.